Estudio comparativo del efecto de la urea y el amoniaco anhidro sobre un cultivo de maiz - Ordoñez, R.=700 1 Gonzalez, P.; Giraldez, J.V.
(Es, En)
ilus., 24 ref.
Keywords: ZEA MAYS; MAIZ; APLICACION DE ABONOS; ABONOS NITROGENADOS; ABSORCION; NITROGENO; ESPAÑA